The impact of the Russia-Ukraine crisis on the stock market : Evidence from Australia - Kamal, Md Rajib; Ahmed, Shaker; Hasan, Mostafa Monzur (Elsevier, 2023)
This paper investigates the effect of the Russia–Ukraine crisis on the Australian stock market. Using the event study methodology, we find significantly negative abnormal returns on the event date (i.e., the first trading day after Russia recognized the two Ukrainian states as autonomous regions) in the Australian stock market. However, this negative stock market reaction mostly disappeared in the post-event period. We also find that small and medium-sized firms were adversely affected during the pre-event and event periods. Interestingly, the magnitude and the direction of the abnormal returns vary across industries. We also find that high-growth, illiquid and export-oriented firms are more exposed to the Russia–Ukraine crisis.
Keywords: Russia–Ukraine crisis; Political uncertainty; Financial contagion; Stock returns; Event study; Australia; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|